Prognostic value of β-Arrestins in combination with glucocorticoid receptor in epithelial ovarian cancer - Ryu, Ji-Won; Shin, Ha-Yeon; Kim, Hyo-Sun; Han, Gwan Hee; Kim, Jeong Won; Lee, Hae-Nam; Cho, Hanbyoul; Chung, Joon-Yong; Kim, Jae-Hoon (Frontiers in Oncology, 2023)
Hormones may be critical factors driving cancer development, and epidemiological findings suggest that steroid hormones play a crucial role in ovarian tumorigenesis. We demonstrated that high glucocorticoid receptor (GR) expression is associated with a poor prognosis of epithelial ovarian cancer. Recent studies have shown that the GR affects β-arrestin expression, and vice versa. Hence, we assessed the clinical significance of β-arrestin expression in ovarian cancer and determined whether β-arrestin and GR synergistically have clinical significance and value as prognostic factors. We evaluated the expression of β-arrestins 1 and 2 and the GR in 169 patients with primary epithelial ovarian cancer using immunohistochemistry. The staining intensity was graded on a scale of 0–4 and multiplied by the percentage of positive cells. We divided the samples into two categories based on the expression levels. β-Arrestin 1 and GR expression showed a moderate correlation, whereas β-arrestin 2 and GR expression did not demonstrate any correlation. Patients with high β-arrestin 1 and 2 expressions exhibited improved survival rates, whereas patients with low GR expression showed a better survival rate. Patients with high β-arrestin 1 and low GR levels had the best prognosis among all groups. β-Arrestin is highly expressed in ovarian cancer, suggesting its potential as a diagnostic and therapeutic biomarker. The combination of β-arrestin and GR demonstrated greater predictive prognostic power than GR expression alone, implicating another possible role in prognostication.